Fe–Fe bonding in the rhombic Fe 4 cores of the Zintl clusters [Fe 4 E 18 ] 4− (E = Sn and Pb) † - Chen, W; Li, Z; Morgan, HWT; Shu, C; Sun, Z; McGrady, JE (Royal Society of Chemistry, 2024)
We report here the synthesis and characterization of two endohedral Zintl-ion clusters, [Fe4Sn18]4− and [Fe4Pb18]4−, which contain rhombic Fe4 cores. The Fe–Fe bond lengths are all below 2.5 Å, distinctly shorter than in the corresponding Cu clusters, indicating the presence of Fe–Fe bonding. Subtle differences in the structure of the Fe4 core between the two clusters suggest that the change in tetrel element causes a change in electronic ground state, with a very short Fe–Fe bond length of 2.328 Å present across the diagonal of the rhombus in the lead case.